KEPEMIMPINAN MELAYANI TERHADAP KINERJA ORGANISASI MELALUI KEADILAN ORGANISASI - Prasetiawaty, Nureka; Hasyim, Abd Wahab; Sabuhari, Rahmat (Cakrawala Management Business Journal, 2025)
This study aims to empirically test and prove the influence of servant leadership on organizational performance, both directly and through organizational justice. This study uses a quantitative approach. The data that can be collected and analyzed amounts to 147 permanent employees who work in several fields at the Trade and Industry Service and the Regional Secretariat of Central Halmahera Regency. Sampling uses a proportional probability technique. SEM-PLS with the SmartPLS 3.0 application is used to test the hypothesis. The results of the study indicate that to improve organizational performance, it can be done by implementing servant leadership that increases the sense of fairness to members of the organization. Servant leadership does not have a significant influence on organizational performance. The organizational justice that is currently felt is able to improve organizational performance. Organizational justice is also able to mediate the influence of servant leadership on significant organizational performance. Theoretically, the results of this study are expected to contribute to the development of human resource management science and organizational behavior so that it can provide benefits to academics and practitioners of regional apparatus organizational management.